The Impacts of Research and Development Expenses on Export and Economic Growth - YÃ¼ksel, Serhat (International Business and Accounting Research Journal, 2017)
The purpose of this study is to identify the effects of research and development expenses on export and economic growth. Within this scope, annual data of 28 European Union member countries for the periods between 1996 and 2014 was taken into the consideration. Additionally, Dumitrescu Hurlin panel causality analysis was used in this study to achieve this objective. First of all, Im, Pesaran and Shin and Levin, Lin & Chu panel unit root tests were used to understand whether the variables are stationary or not. As a result of these tests, it was defined that the variable of economic growth is stationary whereas other two variables (export and R&D) are not. According to the results of Dumitrescu Hurlin causality analysis, it was determined that there is not a significant relationship between economic growth and R&D. On the other hand, it was concluded that there is a causality relationship from export to R&D expenses. This situation shows that EU member countries, which have higher export amount, give more importance to R&D in order to improve themselves.